A Note on Ulmus Villosa Brandis and on other Elms in the N. W. Himalaya - Parker, R. N. (Indian Forester, 1937)
The present position of Ulmus villosa Brandis as a wild and cultivated tree is indicated from which it is inferred that its former occurrence as a wild plant was more extensive than at present. The probable disappearance of U. wallichiana from many areas where it is now found is also predicted. It is suggested that U. pumila now only known as a tree rare in cultivation may be indigenous.